Efficiency of enhanced oil recovery by injection of low-salinity water in barium-containing carbonate reservoirs - Hyemin Park; Yongjun Park; Yeonkyeong Lee; Wonmo Sung (Petroleum Science, 2018)
Abstract When low-salinity water containing sulfate ions is injected into carbonate reservoirs, rock dissolution and in situ precipitation occur, altering rock permeability and wettability. Particularly, when barium ions are present in formation water, they react chemically with $${\text{SO}}_{4}^{2 - }$$ SO42- , and BaSO4 is precipitated. These reactions can cause a serious impact on the efficiency of enhanced oil recovery (EOR). Therefore, the main purpose of this study was to identify EOR efficiency induced by low-salinity waterflooding (LSWF) when Ba2+ is present in carbonate reservoirs. From the experimental results, it was confirmed that the permeability calculated by the measured pressure difference was improved because of rock dissolution predominating over in situ precipitation for the case of low Ba2+ concentrations. In the analysis of wettability alteration through the measurements of relative permeabilities before and after LSWF, the higher Ba2+ concentration case consumed more $${\text{SO}}_{4}^{2 - }$$ SO42- in precipitating the BaSO4, resulting in weaker wettability alteration due to the reduction of sulfate activity. These phenomena ultimately influenced EOR efficiency, i.e., the oil recovery was greater for the lower Ba2+ concentration.